ANALYSIS OF MATHEMATICAL COMMUNICATION SKILLS IN SOLVING MODELING PROBLEMS WITH MARITIME CONTEXT IN ALGEBRA MATERIAL - Adilakirani, Devika; Puji Astuti; Febrian (Jurnal Math-UMB.EDU, 2024)
This research was motivated the importance of mathematical communication skills in improving students' mathematical understanding. The aim of this study is to describe students' mathematical communication skills on algebraic material when solving modeling tasks in the marine context. The research methodology used in this research is descriptive qualitative  research. The research was conducted at SMP Negeri 2 Bintan in June 2024. The research subjects were VIII C students. Data collection techniques were test instruments and interview guidelines. Data analysis techniques are data reduction, data presentation, and inference. The result show that there were 4 students in the high category with a percentage of 19%, 12 students in the medium category with a percentage of 57%, and 5 students in the low category with a percentage of 24%. The researcher suggest that students' mathematical communication skills can be further improved by practicing mathematical problem-solving related to mathematical communication. Keywords: mathematical communication, modeling problems, maritime context, algebra